Breastfeeding and non-nutritive sucking patterns related to the prevalence of anterior open bite in primary dentition - Camila Campos Romero; Helio Scavone-Junior; Daniela Gamba Garib; Flávio Augusto Cotrim-Ferreira; Rívea Inês Ferreira (University of São Paulo, 2011)
OBJECTIVE: Nutritional, immunological and psychological benefts of exclusive breastfeeding for the frst 6 months of life are unequivocally recognized. However, mothers should also be aware of the importance of breastfeeding for promoting adequate oral development. This study evaluated the association between breastfeeding and non-nutritive sucking patterns and the prevalence of anterior open bite in primary dentition. MATERIAL AND METHODS: Infant feeding and non-nutritive sucking were investigated in a 3-6 year-old sample of 1,377 children, from São Paulo city, Brazil. Children were grouped according to breastfeeding duration: G1 - non-breastfed, G2 - shorter than 6 months, G3 - interruption between 6 and 12 months, and G4 - longer than 12 months. Three calibrated dentists performed clinical examinations and classifed overbite into 3 categories: normal, anterior open bite and deep bite. Chi-square tests (p<0.05) with odds ratio (OR) calculation were used for intergroup comparisons. The impact of breastfeeding and non-nutritive sucking on the prevalence of anterior open bite was analyzed using binary logistic regression. RESULTS: The prevalence estimates of anterior open bite were: 31.9% (G1), 26.1% (G2), 22.1% (G3), and 6.2% (G4). G1 would have signifcantly more chances of having anterior open bite compared with G4; in the total sample (OR=7.1) and in the subgroup without history of non-nutritive sucking (OR=9.3). Prolonging breastfeeding for 12 months was associated with a 3.7 times lower chance of having anterior open bite. In each year of persistence with non-nutritive sucking habits, the chance of developing this malocclusion increased in 2.38 times. CONCLUSIONS: Breastfeeding and non-nutritive sucking durations demonstrated opposite effects on the prediction of anterior open bite. Non-breastfed children presented signifcantly greater chances of having anterior open bite compared with those who were breastfed for periods longer than 12 months, demonstrating the benefcial infuence of breastfeeding on dental occlusion.